(untitled) (Research, Society and Development, 2021)
Psychosocial Care Centers (CAPS) are health services that offer care to patients with persistent, moderate to severe mental disorders. Thereby, the present study aimed to analyze the effects of a virtual reality program on postural balance in users of CAPS on the west boarder of Rio Grande do Sul. The study is descriptive, cases series, constituted by 05 male adults, evaluated by means of dynamic computerized posturography, using the tests of sensory organization (TOS) divided into six conditions and the value of the composite score (general index of balance), as well as the sensory analysis of each system (visual, vestibular and somatosensory). Still, the patients were later submitted to ten sessions of exergames, using the Xbox 360 video game, equipped with the Kinect sensor. For data analysis descriptive statistics was used, for the balance variables description, mean values and standard deviation were used. Pearson’s correlation was used to analyze the correlation between the value of the composite score and the postural control systems. The results indicate an improvement in the composite score and in the use of the visual and vestibular systems of the individuals evaluated, after the virtual reality protocol, although it was not statistical significance. In addition, a positive correlation was observed between the composite score and the visual system, indicating that these variables are related to each other. A positive correlation was also identified regarding the values of the composite score and the visual system, pointing out values with a statistically significant difference. In addition, a positive correlation was observed between the composite and the visual system. We can conclude that the practice of exergames contributes to the improvement of postural balance in users of CAPS, constituting an important tool for this purpose.